ANALISIS TEKNOLOGI, ORGANISASIONAL DAN LINGKUNGAN TERHADAP ADOPSI TEKNOLOGI INFORMASI DAN KOMUNIKASI PADA UMKM DI KOTA BANDUNG - Triono, Sunu Puguh Hayu; Yudanegara, Aditya (JURISMA : Jurnal Riset Bisnis & Manajemen, 2019)
Small Medium Enterprise (SME) able to survive the economic crisis when many firms is unable to survive. Therefore, SME aimed to be foundation of Indonesian economic independency. However, SME is now facing some challenges by implementation of ASEAN Economic Community (AEC) in 2015 and industrial revolution 4.0. From literature study, the key to answer those challenges is by adopting Information and Communication Technology (ICT) in their business. According to TOE framework, ICT adoption is affected by three factors, those are technological, organizational and environmental context. This research aimed to analyze the affect of technological, organizational and environmental context to ICT adoption in SME. This research use quantitative and explanatory method to understand the causal relationship among the factors observed. This research held in Binongjati center of knitting industry, Bandung. Population in this research is knitting SME im Binongjati that already using ICT in their business activity. The sample of this research is the owner or manager of those SME. This research analyze 97 samples and using convenient sampling method. Data of those samples then analyzed by multiple regression. This study reveal that technological, organizational and environmental context has significant effect on ICT adoption in SME. Keyword: ICT adoption, SME, TOE framework, technological context, organizational context, environmental context